PEREMPUAN, KEBIJAKAN DAN RUANG PUBLIK: PENGALAMAN DI JANGKANG 1, KUBU RAYA - Ambaryani, Ambaryani (Raheema, 2023)
This study aims to discuss about women, their policies and position in the public sphere. In general, women in Indonesia are lagging behind. They are not involved in policy making because they are placed backstage. Public spaces are usually filled by men. However, what is obtained by Jangkang I, Kubu Raya shows the opposite. Based on interviews with a number of PKK members, and observations of village activities in 2019, it was found that women in Jangkang I had a dominant role in making decisions and playing a role in the public space of the village community. Jangkang I woman once held the position of leader (village head). Through the Family Welfare Empowerment (PKK) activities women also get media for organizations that make them continue to play a role in public affairs and represent the village in several activities in the Kubu sub-district and the Kubu Raya district. They were the ones who helped determine village policies and appeared in public to carry out these policies. The experience in Jangkang I, Kubu Raya, West Kalimantan, can be an inspiration for women in other regions, and a source of study to see the other side of gender issues in Indonesia.